Students’ acceptance of gamification in FBM, UITMCM KAG / Siti Nur Nadhirah Abdul Latip - Abdul Latip, Siti Nur Nadhirah (Faculty of Business and Management, 2020)
Learning via gamification has become one of the most popular methods used by current educators as it provides a fun environment for learning, which could also lead to increased learning performance. The intention of this study is to examine the factors affecting students’ acceptance of gamification among students in the Faculty of Business and Management, Universiti Teknologi Mara Cawangan Melaka Kampus Alor Gajah. Three different independent variables which consisted of performance expectancy, social influence and perceived enjoyment which could influence student’s acceptance were analysed. Proportionate stratified random sampling was used and the sample size consisted of 248 samples from the total population of 700 semester 5diploma students in the Business and Management Faculty. The data obtained were analysed by using the Statistical Package from Social Science Version 23 (SPSSv23). Results revealed that all variables which were the performance expectancy, social influence and perceived enjoyment have a moderate positive relationship with students’acceptance of gamification. The findings also highlighted that the major influenced factor in students’ acceptance of gamification was performance expectancy.